Effects of short-term in-season weightlifting training on the muscle strength, peak power, sprint performance, and ball-throwing velocity of male handball players - Hermassi, S.; Schwesig, R.; Aloui, G.; Shephard, J. R.; Chelly, S. M. (The Journal of Strength and Conditioning Research, 2019)
This study analyzed the effects of in-season weightlifting training, conducted biweekly for 12 weeks. Twenty-two male handball players were divided into experimental (age: 20.3 ± 0.5 years, height: 1.85 ± 0.04 m, and body mass: 86.3 ± 9.4 kg) and control (age: 20.1 ± 0.5 years, height: 1.81 ± 0.05 m, and body mass: 83.9 ± 10.3 kg) groups, and performance was assessed before and after the intervention. Peak power was determined by a cycle ergometer force-velocity test, a vertical squat jump, and a countermovement jump. Measures of 1 repetition maximal strength included bench press, back half-squats, snatch, and clean and jerk. Handball-throwing velocity was assessed by standing, running, and jump throws. The change of direction T-half test and sprint times over 5, 15, and 30 m were recorded by paired photocells. The intraclass correlation coefficient of all parameters exceeded 0.75. Significant training effects were seen for all sprint (3/3) and throwing (3/3) measures, but only 7/14 strength parameters and 3/10 jump parameters. The largest increases of performance were for snatch (n hoch 2 = 0.627; d = 2.85) and 15-m sprinting (n hoch 2 = 0.852; d = 2.73). Countermovement jump force showed a negative response (d = -0.62). Three other parameters (V0 power for the upper and lower limbs, countermovement jump power) showed only small effect sizes (d = 0.45, d = 0.31, and d = 0.23, respectively). We conclude that 12 weeks of biweekly in-season weight training improved the peak power, maximal strength, sprinting, and throwing in handball players, but that their jump performance did not increase with this kind of intervention.The purpose of this study was to evaluate the existence of relative age effects (RAEs) in collegiate soccer. In addition, the impact of nationality, position, class, and National Collegiate Athletic Association (NCAA) tournament qualification status on the prevalence of RAEs was assessed. Birth dates from male NCAA Division I soccer athletes (n = 4,082) from the 2017/2018 season were categorized into quarters based on calendar and scholastic quarters. All athlete birth-date distributions were compared with the expected birth-date distributions for the United States. International-born athletes (INT) displayed a significant difference in birth-date distribution when assessed with calendar quarters, whereas American-born athletes (USA) showed a significant difference in birth-date distributions when assessed with scholastic quarters. Furthermore, INT showed significant RAEs for midfielders and defenders, whereas USA showed significant RAEs midfielders and goalkeepers. In terms of class, INT had significant RAEs for all classes, whereas USA had significant RAEs only for freshmen and sophomores. All INT had significant RAEs regardless of tournament qualification status; however, USA had significant RAEs only for nontournament teams. In summary, significant RAEs exist in male Division I college soccer; however, the presence of RAEs is influenced by nationality, position, class, and NCAA tournament qualification status. Coaches should be aware of RAEs during the recruitment process to avoid potential selection bias.